Linguistic and Cultural Foreign Policies of European States : 18th-20th Centuries - Sanchez-Summerer, Karene; Frijhoff, Willem (Book collections on Project MUSE., 2017)
The policies relating to language pursued by European monarchies and states have been widely studied, but far less attention has been given to their linguistic and cultural policies in territories outside their own borders. This volume takes an interdisciplinary approach to filling that gap, distinguishing and analyzing several different types of linguistic and foreign cultural policies. Such policies, the contributors show, tended not to be proclaimed officially, but they nonetheless had lasting effects on both language and culture in Europe and beyond.